Work-Related Respiratory Disorders in Persons Employed in Quebec Cotton Textile Mills – 1980 to 1995 - Raymond Bégin; Marc Desmeules; Jean-Jacques Gauthier; Gaston Ostiguy (Canadian Respiratory Journal)
Byssinosis, a chronic lung disease of cotton mill workers, is characterized by repeated episodes of reversible airway obstruction, which can lead to permanent alterations of lung function. When this occurs in Quebec the worker must be removed from further exposure in accordance with the provincial compensation rules. The current Quebec Occupational Safety and Health Regulation has a permissible exposure limit of 500 μg/m3, resulting in a prevalence rate of byssinosis of 2% to 5% in cotton workers. In this study the incidence of new respiratory disorders in persons employed in Quebec cotton mills from 1980 to 1995 was assessed and factors that identified byssinosis cases were analyzed. Incidence of the disease was assessed on the basis of cases referred to the Commission de Santé & Sécurité au travail du Québec (Quebec Workers’ Compensation Board) from all Quebec textile plants. Analyses of age, years of employment, job description, smoking history, bronchial reactivity and lung function before and at work were used for diagnostic purposes. Incidence of new byssinosis cases from 1990 to 1995 was 2.8 cases per year per 5000 workers, slightly above the incidence from 1980 to 1989, at 1.7 cases per year. The incidence of chronic cases was stable at 1.5 cases per year, whereas that of early cases increased from 0.3 cases per year (1980 to 1989) to 1.25 cases per year (1990 to 1995). In comparison with chronic byssinosis cases, the average time of work before symptom appearance was 17±4 versus 32±1 years, P<0.001. Bronchial reactivity to methacholine (PC20) at work was below 2 mg/mL in 100% of byssinosis cases versus 14% in subjects not diagnosed with byssinosis. Decreases in forced expiratory volume in 1 s (FEV1) at work averaged 30% in the byssinosis and 6% in the nonbyssinosis subjects; peak flow rates were not different between those with and those without byssinosis. Early byssinosis cases were from three distinct plants in different townships, and 45% of cases worked in cardroom occupations. PC20 equal to or less than 2 mg/mL at work was strongly associated with the decrease in FEV1 during a work shift. In conclusion, current cotton processing work in Quebec is associated with a significant incidence of byssinosis. PC20 of 2 mg/mL or less at work was closely associated with airflow limitation at work.